The golden rule of public investment: protecting fiscal leeway and public infrastructure in the EU - Feigl, Georg; Truger, Achim (Brussels, 2015)
"The fiscal constraints imposed by the new European economic governance have had a detrimental effect on public investments in the member states in recent years.